Upaya Guru dalam Meningkatkan Aktivitas Belajar Pada Pembelajaran Tematik Menggunakan Metode Tanya Jawab Pada Masa Pandemi Covid 19 Siswa Kelas V SDN 28/III Talang Kemuning - Rita Tarmika; Nazurty Nazurty; Marzul Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research was carried out based on the implementation of the learning process carried out by teachers in schools. The problems encountered are still many students who have difficulty in participating in learning activities, especially thematic learning. This is evident from the low scores of students in the evaluation of student learning outcomes. This research is a classroom action research (CAR) which aims to determine the use of the question and answer method in increasing learning activities for elementary school students during the covid-19 pandemic. The research was carried out in two cycles. The research subjects were 6 students of class V SDN 28/III Talang Kemuning, where the data taken was in the form of observation data through teacher performance observation sheets and student activities and evaluation sheets in the form of thematic learning assessment sheets carried out in each learning process. This research was conducted in 4 stages, namely planning, implementation, observation and evaluation and reflection. The results of this study indicate that the use of the question and answer method can increase the learning activities of fifth grade students at SDN 28/III Talang Kemuning during the covid-19 pandemic.